Attosecond metrology of vacuum-ultraviolet high-order harmonics generated in semiconductors via laser-dressed photoionization of alkali metals - Arjun Nayak; Debobrata Rajak; Balázs Farkas; Camilio Granados; Philipp Stammer; Javier Rivera-Dean; Theocharis Lamprou; Katalin Varju; Yann Mairesse; Marcelo F. Ciappina; Maciej Lewenstein; Paraskevas Tzallas (Nature Communications)
Abstract Semiconductor crystals driven by strong mid-infrared pulses offer advantages for studying many-body physics and ultrafast optoelectronics via high-harmonic generation. While the process has been used to study solids in the presence strong mid-infrared fields, its potential as an attosecond light source is largely underexplored. We demonstrate that high-harmonics emitted from zinc-oxide crystals produce attosecond pulses, measured through spectroscopy of alkali metals. Using a cross-correlation approach, we photoionize Cesium atoms with vacuum-ultraviolet high-harmonics in the presence of a mid-infrared laser field. We observe oscillations in the photoelectron yield, originating from the instantaneous polarization of atoms by the laser field. The phase of these oscillations encodes the attosecond synchronization of the high-harmonics and is used for attosecond pulse metrology. This source opens new spectral windows for attosecond spectroscopy, enabling studies of bound-state dynamics in natural systems with low ionization energies, while facilitating the generation of non-classical entangled light states in the visible-VUV.